Teleosemantics : new philosophical essays - Macdonald, Graham; Papineau, David, 1947- (Clarendon Press, 2006)
'Teleosemantics' seeks to explain meaning and other intentional phenomena in terms of their function in the life of the species. This volume of new essays from a line-up of well-known contributors offers a summary of the current state of the teleosemantics debate.